2001
DOI: 10.1080/003655201300191941
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Analysis on the Efficacy of the Second-line Treatment Regimens for Helicobacter pylori Infection

Abstract: Ranitidine bismuth-based triple therapies, as well as quadruple therapies, seem to be the most effective re-treatment therapies in all currently undertaken therapies. The strategy of adding two new antimicrobials to previous regimens was also effective in re-eradication therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 37 publications
4
67
1
1
Order By: Relevance
“…[1][2][3]95 Here, quadruple therapy is recommended, although the second eradication may also fail in up to 30-40% of the cases as was shown by expert opinion, 96 a systematic review 97 and our own experience. 78 F-based second-line therapies obtained eradication rates as high as the primary regimens, suggesting that this compound could be usefully included in the second-line combinations.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]95 Here, quadruple therapy is recommended, although the second eradication may also fail in up to 30-40% of the cases as was shown by expert opinion, 96 a systematic review 97 and our own experience. 78 F-based second-line therapies obtained eradication rates as high as the primary regimens, suggesting that this compound could be usefully included in the second-line combinations.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of the efficacy of second-line H. pylori eradication regimens by Hojo et al 17 concluded that ranitidine-bismuth-based triple and quadruple therapies appeared to be the most effective second-line options. Therapies containing bismuth are not available for use in Japan, however, and the only authorized re-treatment regimens comprise PPI + AMPC + CAM (PPI/AC).…”
Section: Discussionmentioning
confidence: 99%
“…La eficacia de esos tratamientos ha disminuido conforme ha aparecido resistencia de H.pylori a los diferentes antibióticos 7 , de modo que actualmente alrededor del 20% de los pacientes no consiguen la erradicación tras el manejo inicial y de ellos, alrededor del 24 al 30% continúan sin conseguirla tras un segundo manejo 9,10 . Teniendo en cuenta la participación definida de H. pylori en las patologías graves mencionadas, así como el impacto que podría tener la utilización de antibióticos sobre la microbiota intestinal, la vacunación es una estrategia necesaria, que además puede prevenir posibles reinfecciones que hasta el momento no son evitables con las terapias de erradicación 11 , por lo que sería una solución para las consecuencias en la salud pública mundial que ha generado esta bacteria.…”
Section: Introductionunclassified